Hellenism under siege: The national-populist logic of antiglobalization rhetoric in Greece - Tsatsanis, E. (Journal of Political Ideologies, 2011)
Using as a focal point the controversy over the content of an elementary-school level history textbook in Greece, the main argument put forth in this article is that the campaign to withdraw this textbook was preceded by and further facilitated an ongoing process of ideological convergence between forces of the left and the right. It is argued that these forces increasingly structure their political discourse on the basis of a unified 'interpretative frame' and align their efforts to politicize cultural, symbolic and educational issues as part of a broader project of cultural protectionism. By examining the different stages of the mobilization effort, the article documents the process of frame emergence and discusses its potential for a more profound and lasting ideological transformation in Greece. At a more theoretical level, the article also considers the usefulness of the concept of 'interpretative frames', particularly in its ability to address the familiar micro-macro divide in studies of ideology and to illuminate the mechanisms of ideological change.